2001
DOI: 10.1046/j.1365-2672.2001.01386.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dissolved CO2 concentration on the death kinetics of Saccharomyces cerevisiae

Abstract: Aims: The effects of temperature and concentration of dissolved CO 2 on the inactivation of Saccharomyces cerevisiae were investigated using a plug-¯ow system. Methods and Results: Several combinations of pressure (4, 6, 8, 10 mega-Pa (MPa)) and temperature (30, 34, 36, 38°C) were used. The D-values obtained were 0á14 min at 8 MPa and 38°C, and 0á15 min at 10 MPa and 36°C. The log D-values were related linearly to the treatment temperature and to the dissolved CO 2 concentration. The thermal resistance consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 16 publications
0
32
0
Order By: Relevance
“…4). We have reported that pressure influenced the inactivation of enzymes on batch treatment, 10) but it was found that the concentration of CO 2 dissolved in the sample during continuous flow treatment 15,16) was higher than that during batch treatment 10) at the same pressure. Therefore, such inconsistency can be attributed to the difference in the mode of treatment.…”
Section: Effects Of Co 2 Feeding Ratio and Pressure On Inactivation Omentioning
confidence: 94%
See 1 more Smart Citation
“…4). We have reported that pressure influenced the inactivation of enzymes on batch treatment, 10) but it was found that the concentration of CO 2 dissolved in the sample during continuous flow treatment 15,16) was higher than that during batch treatment 10) at the same pressure. Therefore, such inconsistency can be attributed to the difference in the mode of treatment.…”
Section: Effects Of Co 2 Feeding Ratio and Pressure On Inactivation Omentioning
confidence: 94%
“…Furthermore, we developed a new apparatus for a continuous flow system with microbubbles of pressurized CO 2 . -Amylase (AA) and acid protease 14) were efficiently inactivated in a saline, and L. brevis and S. cerevisiae 15,16) were also effectively inactivated by this system.…”
mentioning
confidence: 99%
“…There have been many studies on the effects of high pressure carbon dioxide treatment (HPCT) on the inactivation of bacteria under moderate temperature (approximate 20 to 40˚C) and pressure (approximately 5 to 35 MPa) (Nakamura et al, 1994;Ishikawa et al, 1995;Erkmen, 2001;Shimoda et al, 2001Shimoda et al, , 2002. For the sterilization of bacterial spores, it has been thought to be effective to decrease the heat tolerance of bacterial spores, and then to inactivate them by subsequent HT.…”
mentioning
confidence: 99%
“…As a consequence, the treatment time and temperature required for microbial inactivation could be substantially reduced (15,16,26). Recently, it was shown that the antimicrobial effect was not related to the pressure of CO 2 but to the concentration of dissolved CO 2 (dCO 2 ) (27). The experiments were carried out with saturated dCO 2 concentrations under various combinations of pressure and temperature conditions.…”
mentioning
confidence: 99%
“…Shimoda et al (27) have reported that the inactivation temperature of Saccharomyces cerevisiae was reduced by about 30°C under high-pressure carbonation. As mold spores have only a moderate thermal resistance, the heat treatment in fruit juice production is intended primarily to inactivate mold spores.…”
mentioning
confidence: 99%